2007
DOI: 10.1143/jjap.46.2019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Improvement in Hot-Carrier Reliability of Sub-Micrometer High-Voltage Double Diffused Drain Metal–Oxide–Semiconductor Field-Effect Transistors

Abstract: The hot-carrier reliability of 12 V high-voltage n-channel double diffused drain metal-oxide-semiconductor (DDDMOS) field-effect transistors with various n-type double diffusion (NDD) implant dosages is investigated. A high NDD implant dosage results in a high substrate current; however, on-resistance (R on ) degradation is low. The damage location shifting toward the channel is responsible for this unexpected low R on degradation. Technology computer-aided design (TCAD) simulation and charge pumping measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…6 that I Dlin degrades the most, suggesting that hot-carrier-induced damage is mainly located in the N − drift region. 25) The degradations of I Dsat , G mmax , and V t (less than a 3 mV shift, not shown) are much smaller than the I Dlin degradation. Thus, I Dlin degradation is chosen for judging the severity of hotcarrier-induced device degradation in the following analyses.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…6 that I Dlin degrades the most, suggesting that hot-carrier-induced damage is mainly located in the N − drift region. 25) The degradations of I Dsat , G mmax , and V t (less than a 3 mV shift, not shown) are much smaller than the I Dlin degradation. Thus, I Dlin degradation is chosen for judging the severity of hotcarrier-induced device degradation in the following analyses.…”
Section: Resultsmentioning
confidence: 86%
“…Several studies showed that the V G at which the maximum hot-carrierinduced device degradation is produced is that at which the peak I sub is produced. [24][25][26][27] Some other groups claimed that a higher V G value results in greater hot-carrier-induced device degradation. 28,29) Results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the devices are operated under high voltages, the off-state breakdown voltage is a key device parameter. Furthermore, hot-carrier induced device degradation, caused by the damage near the Si-SiO 2 interface and/or charge trapping in the gate oxide due to a high electric field near the drain end of the channel, is prone to developing into a serious reliability concern [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For the design of n-type highvoltage MOS transistors, a lightly doped n − drift region next to the drain is usually employed to achieve the required breakdown voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the drift region, such as by varying the doping concentration or the length of drift region, in high-voltage MOS transistors has been shown to produce a serious impact on V BD and hot-carrier-induced degradation of the device. [23][24][25][26][27][28] Our previous work has shown that high-voltage n-type MOS transistors using a gradual junction structure in the drift region have improved V BD without sacrificing device drivability. 29) In this study, high-voltage n-type MOS transistors with traditional and gradual junctions in the N − drift region are further investigated for devices with two different dimensions.…”
Section: Introductionmentioning
confidence: 99%